Analysing the impact of renewable energy use, CO₂ emissions, oil production, and oil prices on sustainable economic growth: Evidence from Saudi Arabia using the ARDL approach - Gafsi, Nesrine (Edelweiss Applied Science and Technology, 2025)
This study investigates the dynamic relationship between renewable energy consumption, CO₂ emissions, crude oil production, and oil prices, and their combined impact on sustainable economic growth in Saudi Arabia. Employing the Autoregressive Distributed Lag (ARDL) bounds testing approach, the study utilizes annual time-series data from reliable global sources. Unit root tests confirmed that all the variables are integrated of order one, which justifies the use of the ARDL model. Empirical findings indicate that renewable energy usage and oil prices have statistically significant positive effects on both short- and long-term economic growth, while CO₂ has a negative effect. There is no statistically significant relationship with oil production. The error correction term reveals that there is a stable process of long-run adjustment. These results emphasize the importance of transitioning towards cleaner energy sources while maintaining macroeconomic resiliency to oil market fluctuations. The research offers policy-enabling insights towards environmental and economic sustainability in Vision 2030 Saudi Arabia.